Systematic Desensitization Technique's Effectiveness in Reducing Public Speaking Anxiety in MAN 1 Pamekasan Students - Ishlakhatus Sa'idah; Adibah Nurul Izzah (UIN Antasari Banjarmasin, 2023)
The purpose of this study was to determine the effectiveness of the systemic desensitization technique in reducing public speaking anxiety among students of MAN 1 Pamekasan. Furthermore, the purpose of this study is to see if there are any significant differences in public speaking anxiety scores between before and after students of MAN 1 Pamekasan receive systematic desensitization techniques. This research was conducted in a group counseling setting. This study used an experimental design with a one-group pre-test-post-test design. In this study, the primary data source was the public speaking anxiety scale, and the secondary data source was interviews. The data analysis technique used in this study is non-parametric data analysis using the Wilcoxon test. The researchers used non-parametric data analysis because the number of subjects to be studied was only eight. The results of the study show that the systemic desensitization technique can effectively reduce public speaking anxiety. This can be seen from the results of asymp. sig. 0.011 < 0.05, which means that Ha is accepted with an average increase of 4.50.